Rising hegemon?: China’s international ambition and the politics of hegemonic ordering in Asia during the COVID-19 pandemic - Harnisch, Sebastian (Hegemonic transition, 2021)
The chapter investigates the rivaling hegemonic role claims by the US and the People’s Republic of China during the COVID-19 pandemic. In this interactionist role theory account, I argue that Trumpian populism has tried to altercast China into the role of an “international perpetrator.” In turn, China’s leadership has countered this role ascription by presenting China as a defender of a rules-based order and as an important provider of global public goods. The chapter contends that while the Trump administration has failed as a public goods provider to its own people and the international community at large, this does not (automatically) enable China to raise international acceptance for its own role contention. The way the US neglected its leadership role by trying to shift blame onto China, and engaging in populist-inspired vaccine nationalism, incentivized the Chinese government to overreach its role (re-)making by promoting Chinese selective largesse, when most nations expected a more humble demeanor. This way, the US’ leadership failure enabled China to try to lead. Thus far, however, China’s leadership ambitions have found only limited international acceptance. Despite China’s claim to the contrary, most countries view that Beijing’s COVID-19 policies were not directed toward providing global public health goods. In this perspective, the Chinese government rather produced a varying mix of private and club health goods for itself and specific countries who assuage its reputational expectations and its commercial interests. While this is not unusual for governments around the globe, it bodes ill for an actor claiming largesse as a public goods provider and seeking approval for its global leadership.
Gesehen am 05.06.2023